Diagnostic immunohistopathology - Mason, David (Henry Stewart Talks, 2007)
Techniques for identification and immunocytochemical study of proteins, Leucocyte-associated molecules, Immunhistological labeling, Immunohistological studies of human tissue, The first monoclonal anti-leucocyte antibodies, Paraffin reactive monoclonal antibodies, Protein conformation and antigenicity, Immunohistological markers for the study of solid tumors, Carcinoma, seminoma, mesothelioma, melanoma and carcinoid tumors, Immunohistological markers for the diagnosis of lymphoid neoplasms, Anaplastic large cell lymphoma, New labeling techniques, New antibodies and molecular targets
Archived at 2019/06/13